The Construction Of Efficiently Computable Endomorphisms For Scalar Multiplication On Some Elliptic Curves - Antony, Siti Noor Farwina Mohamad Anwar (2019)
Elliptic curves scalar multiplication (ECSM), denoted as kP, is one of the building blocks in Elliptic Curve Cryptography (ECC). An elliptic curve, E defined over a finite prime field, Fp have finitely many points which form an abelian group and there exists a prime subgroup with order n. ECSM involves the multiplication of scalar k 2 [1;n